Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Féminisme autochtone militant: Quel féminisme pour quelle militance? - Arnaud, Aurélie (Nouvelles pratiques sociales, 2014)
Parler du mouvement des femmes autochtones au Canada comme de l’émergence d’un féminisme autochtone ne va pas forcément de soi, surtout pour les principales intéressées, soit les militantes pour la reconnaissance des droits des femmes autochtones. Pourtant les critiques qu’elles font du système patriarcal imposé à leurs nations par la colonisation et les espaces politiques qu’elles ont progressivement conquis les rapprochent des féministes québécoises avec lesquelles elles ont su forger des alliances au fil du temps.
Keywords: approches et analyses; communication; cours; discipline; féminisme autochtone; histoire et politique; militance; patriarcat; pol4105; premier cycle; premières nations; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques